Arm coordination in elite backstroke swimmers - Chollet, D.; Seifert, L. M.; Carter, M. (Journal of Sports Sciences, 2008)
In this study, we assessed arm coordination in the backstroke over increasing speeds by adapting the index of coordination originally used in the front crawl. Fourteen elite male backstroke swimmers swam four trials of 25 m at the speeds corresponding to the 400-m, 200-m, 100-m, and 50-m events. The six phases of the arm stroke were identified by video analysis and then used to calculate the index of coordination, which corresponded to the time between the propulsive phases of the two arms. With increases in speed, the elite swimmers increased the stroke rate, the relative duration of their arm pull, and their index of coordination, and decreased the distance per stroke (P < 0.05). Arm coordination was always in catch-up (index of coordination of -12.9%) because the alternating body-roll and the small shoulder flexibility did not allow the opposition or superposition coordination seen in the front crawl. This new method also quantified the relative duration of the hand's lag time at the thigh, which did not change (~2%) with increasing speed for the elite swimmers. The index of coordination enables coaches to assess mistakes in backstroke coordination, particularly in the hand's lag time at the thigh.